Rethinking the Mechanisms Underlying the McGurk Illusion - Gonzales, Mariel G.; Backer, Kristina C.; Mandujano, Brenna; Shahin, Antoine J. (Frontiers in Human Neuroscience, 2021)
The McGurk illusion occurs when listeners hear an illusory percept (i.e., “da”), resulting from mismatched pairings of audiovisual (AV) speech stimuli (i.e., auditory/ba/paired with visual/ga/). Hearing a third percept—distinct from both the auditory and visual input—has been used as evidence of AV fusion. We examined whether the McGurk illusion is instead driven by visual dominance, whereby the third percept, e.g., “da,” represents a default percept for visemes with an ambiguous place of articulation (POA), like/ga/. Participants watched videos of a talker uttering various consonant vowels (CVs) with (AV) and without (V-only) audios of/ba/. Individuals transcribed the CV they saw (V-only) or heard (AV). In the V-only condition, individuals predominantly saw “da”/“ta” when viewing CVs with indiscernible POAs. Likewise, in the AV condition, upon perceiving an illusion, they predominantly heard “da”/“ta” for CVs with indiscernible POAs. The illusion was stronger in individuals who exhibited weak/ba/auditory encoding (examined using a control auditory-only task). In Experiment2, we attempted to replicate these findings using stimuli recorded from a different talker. The V-only results were not replicated, but again individuals predominately heard “da”/“ta”/“tha” as an illusory percept for various AV combinations, and the illusion was stronger in individuals who exhibited weak/ba/auditory encoding. These results demonstrate that when visual CVs with indiscernible POAs are paired with a weakly encoded auditory/ba/, listeners default to hearing “da”/“ta”/“tha”—thus, tempering the AV fusion account, and favoring a default mechanism triggered when both AV stimuli are ambiguous.